2022
DOI: 10.3390/pr10030511
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Testing of Discrete Element Simulation Parameters for Urea Particles

Abstract: The lack of accurate simulation model parameters in the optimization design process of variable fertilizer application devices has resulted in large errors between simulation and theoretical calculation results, which has restricted the development of variable fertilizer application devices to a certain extent. Additionally, there are few scholars studying urea granules, so many parameters of urea granular fertilizer cannot be directly obtained from the literature. The aim of this study is to calibrate a set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Jiahui Ren et al measured the basic physical parameters and repose angle of sugar cane leaves through physical experiments, and conducted DEM simulation using the repose angle as the response value, which offered reference for parameter calibration of the strip-and blade-shaped straw materials [17]. Haoran Bu et al explored the contact parameters between urea grains and variable-rate fertilization by combining EDEM simulation and bench experiments [18]. To improve the accuracy of parameters used in DEM simulation of sunflower clearing, Xiaoxiao Sun et al conducted physical experiments and DEM simulation to calibrate the parameters of sunflower [19].…”
Section: Introductionmentioning
confidence: 99%
“…Jiahui Ren et al measured the basic physical parameters and repose angle of sugar cane leaves through physical experiments, and conducted DEM simulation using the repose angle as the response value, which offered reference for parameter calibration of the strip-and blade-shaped straw materials [17]. Haoran Bu et al explored the contact parameters between urea grains and variable-rate fertilization by combining EDEM simulation and bench experiments [18]. To improve the accuracy of parameters used in DEM simulation of sunflower clearing, Xiaoxiao Sun et al conducted physical experiments and DEM simulation to calibrate the parameters of sunflower [19].…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic parameters of black soil particles can be obtained experimentally, while some of the discrete elemental simulation parameters are not easily obtained. Therefore, the discrete element contact parameters of black soil were optimized for different particle sizes of black soil particles by using the multi-indicator total evaluation normalization method and response surface method [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The fertilizer discharger is one of the critical components of fertilizer application machinery, and the existing fertilizer extractors are mainly divided into grooved wheel type and spiral type [4,5]. Both suffer from uneven fertilizer discharge due to their structural defects and cannot break down caking fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters of the Bond model for caking fertilizer have been determined. For the simulation process of granular fertilizer and caking fertilizer, the contact between granular fertilizer and granular fertilizer, caking fertilizer and caking fertilizer, granular fertilizer and caking fertilizer, granular fertilizer, and fertilizer discharge device, and caking fertilizer and fertilizer discharge device all occurred during the simulation test, the parameters obtained by referring to the team's previous research and related studies[26][27][28][29]are shown in Table2.…”
mentioning
confidence: 99%